Dielectric laser acceleration of 28 keV electrons with the inverse Smith-Purcell effect - Breuer, John; Hommelhoff, Peter (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2014)
Dielectric laser acceleration exploiting the large optical field strength of short laser pulses and the proximity of a dielectric structure can support high acceleration gradients may therefore lead to much smaller accelerators, with future potential application in table-top free electron lasers. We report a proof-of-concept experiment demonstrating dielectric laser acceleration of non-relativistic 28 keV electrons derived from a conventional scanning electron microscope column at a single fused-silica grating. The electrons pass the grating as closely as 50 nm and interact with the third spatial harmonic, which is excited by 110 fs long 800 nm laser pulses with a peak electric field of 2.85 GV/m. The observed maximum acceleration gradient of 25 MeV/m is already comparable to state-of-the-art radio-frequency structures. This work thus represents a demonstration of scalable laser acceleration and of the inverse Smith-Purcell effect in the optical regime. For relativistic electrons and otherwise identical conditions up to two orders of magnitude larger acceleration gradients are expected. © 2013 Elsevier B.V.
UnivIS-Import:2015-03-09:Pub.2014.nat.dphy.IAP.exphys.dielec_7
Keywords: Dielectric grating accelerator; Inverse Smith-Purcell effect; Laser-driven particle acceleration; Non-relativistic electrons